Direito intertemporal no âmbito do direito urbanístico - Rocha, Rúsvel Beltrame (2011)
The Main Purpose of this study is to discuss the acquired rights on the Urban Laws. The Supremo Tribunal Federal rules that the rights on the urban law happens with the start of the works, dully licensed by the local public office. On the other hand, most cities in Brazil defines that this moment really happens when the owner submitt the License Permit to the City Offices. Based on the Constitutional Principles of Urban Planning, the intent of this paper is to demonstrate that the the proper moment for the acquisition of the rights is exactily when the license is granted by the local autorirty. Is is also sugested that all the process of annalises of construction permits should be suspended during the phases of alteration or revision of City Regulation Plans